2016
DOI: 10.1556/032.2016.66.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Mutual trustworthiness as a governance mechanism in business relationships — A dyadic data analysis

Abstract: Purpose -Several researchers have pointed out that trust is a relational attribute that has to be analyzed in situations associated with risk and vulnerability; and that analyzing it needs a dyadic operationalization and analysis, especially when mutuality is a key concept of the research design. Based on a literature review we develop a state of the art research profile that illustrates, today's survey based trust related empirical research has severe limitations, it usually carries out general relationship a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…This article will not cover the economic theoretical background of the study; it can be found in and Gelei-Dobos's [2016] article. Still, it is important that the hypothesis of our study was the following: When the level of trustworthiness between the partners is mutually strong in a given business relationship, then it is true for that business relationship that high-risk actions occur (and are carried out).…”
Section: The Study Used As the Basis Of Comparison And The Results Rementioning
confidence: 99%
See 1 more Smart Citation
“…This article will not cover the economic theoretical background of the study; it can be found in and Gelei-Dobos's [2016] article. Still, it is important that the hypothesis of our study was the following: When the level of trustworthiness between the partners is mutually strong in a given business relationship, then it is true for that business relationship that high-risk actions occur (and are carried out).…”
Section: The Study Used As the Basis Of Comparison And The Results Rementioning
confidence: 99%
“…Based on these, Table 1 summarises the present methodological profile. Zineldin-Jonsson [2000] x -x x Handfield-Bechtel [2002] x -x x Brashear et al [2003] x -x x Dyer-Chu [2003] x -x x Farrelly-Quester [2003] x -x x Izquierdo-Cillán [2004 ] x -x x Kwon-Suh [2004] x -x x Ryssel-Ritter-Gemünden [2004] x -x x Gounaris [2003] x -x x Leung et al [2005] x -x x Svensson [2005] x -x x Barnes-Naudé-Michell [2005] x -x x Ulaga-Eggert [2006] x -x x Svensson [2006] x -x x x Zhao-Cavusgil [2006] x -x x Caceres-Paparoidamis [2007] x -x x Eriksson-Laan [2007] x -x x Kingshott-Pecotich [2007] x -x x Liu-Luo-Liu [2009] x -x x Nielsen-Nielsen [2009] x -x x Panayides-Lun [2009] x -x x Yeung et al [2009] x -x x Wagner-Eggert-Lindemann [2010] x -x x Davis et al [2011] x -x x Jiang-Henneberg-Naudé [2012] x -x x Source: Gelei-Dobos [2016] p. 672.…”
Section: The Statistical-mathematical Methodology Applied In the Analmentioning
confidence: 99%
“…Trust means the dimension to which extent parties of the given relationship perceive one another to be credible and benevolent partner (Ganesan, 1994). Therefore, trust is undoubtedly an important variable in governing the interactional dynamics (Andersen & Kumar, 2006;Gelei & Dobos, 2016).…”
Section: Cooperationmentioning
confidence: 99%